Design and implementation of an electronic voting system for student elections - Aliaksei Khomchanka (Hochschule für angewandte Wissenschaften Hamburg, 2019)
As e-voting becomes more widespread in recent decades, there are multiple attempts to implement e-voting in elections of various scales. One of such use cases is university elections for student organizations. A good class of platforms for implementing such voting systems is public clouds, such as Amazon Web Servers. This report shows the motivation behind the implementation of such a system, its technical requirements and methods of making such a system serverless.